Alleviation of Adverse Effect of Drought Stress on Soybean (Glycine max. L.) by Using Poultry Litter Biochar - Mannan, MA; Halder, E; Karim, MA; Ahmed, JU (Bangladesh Agronomy Journal, 2017)
The experiment was conducted under controlled condition at the Department of Agronomy, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Bangladesh from January to April 2015 to clarify the mechanism that might be involved in the ameliorating effects of poultry litter biochar on soybean plants grown under water deficit stress. The treatments were (i) water regimes (well watered and 40% field capacity) and (ii) biochar (0, 25, 50 and 100 t ha-1). Results indicated that water deficit stress induced reduction in growth, leaf water and chlorophyll content and yield of soybean plant compared with those of the unstressed plants. On the other hand, water deficit stress led to increases in proline content. The improvement of drought tolerance resulted from biochar application were accompanied with improved water and proline accumulation as well as less degradation of chlorophyll in leaf was observed. These results clearly demonstrate that harmful effect of drought could reduce on plant height, leaf water and chlorophyll contents and yield of soybean. Consequently, application of poultry litter biochar is a good strategy to effectively solve the seasonal drought stress problem in dry lands. Bangladesh Agron. J. 2016 19(2): 61-69